THE REFLECTION OF COVID-19 IN LITERARY WORKS: THE SAMPLE OF SHORT STORY - Sayır, Muhammed Fatıh; Aydın, Nurullah (My University, 2024)
Although it is not on the agenda these days, COVID-19 affected the whole world between 2020 and 2022. This disease, which spread to the whole world in a short time and turned into a pandemic, was an extraordinary experience for humanity. Restriction decisions taken by governments, use of masks, social distance, and various hygiene rules entered our lives with COVID-19. COVID-19 caused many people to lose their lives, and because of the social and economic difficulties during pandemic people had difficult times. It is very possible that this disease, which affected all areas of life, also have reflections in literary works. In this study, The 2021 Story Yearbook of Edebiyat Ortamı magazine published in Türkiye was examined in this context. In the study, document analysis, one of the qualitative research methods, was used.While examining the story yearbook, the characteristics of the COVID-19 disease and its effects on society were taken into consideration. In the story yearbook, which contains 78 stories published in different literary magazines in 2020, it has been seen that there are 5 stories referring to COVID- 19. These stories are Gelip Geçenin Sözü, Zor Günler Daha Zor Geçer, Virüs, Korona Günleri, and Korona Günlükleri. In these stories, which were examined in terms of the reflections of COVID-19, it was determined that the authors handled different aspects of the pandemic in their works. The presence of five stories related to the COVID-19 pandemic in the relevant story yearbook can be considered as a sign that similar literary works may be written in the future.
Keywords: COVID-19, Reflection, Literary Works, The 2021 Story Yearbook of Edebiyat Ortamı, Short Story.